Autoimmune Parkinsonism: A Newer Manifestation of Contactin-Associated Protein-Like 2 Autoimmunity: A Case Report - Maturu, Mohan V Sumedha; Datla, Aravind Varma; Devabhaktuni, Rajesh Babu; Maturu, Prajwala; Mandwe, Deepak Sahebrao (International Clinical Neuroscience Journal, 2023)
Contactin-associated protein-like 2 (CASPR2) antibodies are part of an expanding spectrum of disorders. Although they were initially associated with Morvan’s syndrome and peripheral nerve hyperexcitability, their clinical manifestations are more varied than previously recognized. In this report, we present a rare case of a middle-aged woman who experienced gait disturbances, sleep disturbances, behavioral changes, and postural abnormalities over a period of five months. A thorough examination revealed a Parkinsonian phenotype. Considering the timeline and symptomatology, an autoimmune work-up was conducted, which detected CASPR2 antibodies in the patient’s serum. Treatment with high-dose intravenous Methylprednisolone followed by rituximab effectively reversed her clinical manifestations without residual neurological deficits.